Hubungan antara Karakteristik Petani dengan Motivasinya dalam Membudidayakan Tanaman Tebu (Kasus Kelompok Tani Dewi Ratih 1, Desa Maospati, Kecamatan Maospati, Kabupaten Magetan) - KURNIASIH, DIAN; SUDARTA, WAYAN; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017DO - 10.24843/JAA.2017.v06.i04.p07, 2017)
Correlation Between Farmer Characteristic With Their Motivation In Cultivate A Sugar Cane (In Case Of Dewi Ratih 1 Farmer Group At Maospati Village, Subdistrict Of Maospati, Magetan Regency) Sugar cane plant plays an important role in meeting the sugar consumtion needs of society and industrial sector. In order to support the improvement of sugar cane plant production, the government should provide an input or direction that is needed by sugar cane farmers as a motivation for farmers to increase the production of sugar cane as a raw material for sugar. The characteristics of the farmers have become one of important factors that affect the farmer motivation in cultivation of sugar cane plant in farmer’s group of Dewi Ratih 1, Maospati Village, Maospati Districts, Magetan Regency. Which is expected to be a reference for the government and the farmers in determine the policies and development strategies in order to make sugar cane farming can improve revenue and the welfare of the farmers. The purpose of this research is to identify the characteristics of the farmer, motivation of the farmers in cultivating sugar cane plant and determine the correlation between the farmers characteristics and the farmer motivation in cultivating sugar cane plant in farmer’s group of Dewi Ratih 1, Maospati village, Maospati districts, Magetan regency. This sampling by using simple random method. Data analysis method that is used is descriptive analysis and spearman rank correlation coefficient test. The result of descriptive analysis shows that the farmers characteristics included in the low category, while the farmer motivation in cultivation of sugar cane plant included in the medium category. The result of spearman rank correlation analysis shows that the characteristics of the farmers who have a significant correlation with the motivation of the farmers is age, household income, vast of arable land, the number of household members, and farming experience.